Ecological reef restoration: consumptive and nonconsumptive interactions among common North Sea predators and European oysters - Ellrich, Julius A.; Kozian-Fleck, Clemens; Brand, Markus; Colsoul, Bérenger; Pogoda, Bernadette (Frontiers in Environmental Science, 2025)
Oyster reefs are biodiversity hotspots with multiple ecosystem functions and services that are declining worldwide. Historic populations of European oysters (Ostrea edulis) have been decimated by overfishing and are nowadays considered functionally extinct in European waters. To halt and reverse the associated biodiversity loss, oyster reef restoration was implemented into marine conservation measures and several reef restoration projects started across Europe. Following ecological restoration standards, it is crucial to identify reef-associated predators and predator-prey interactions influencing reef recovery as predators can control prey populations. Therefore, this study examined consumptive and nonconsumptive interactions among common North Sea predators, brown crabs (Cancer pagurus) and European lobsters (Homarus gammarus), and European oysters on Helgoland island (German Bight, North Sea) for the first time. Field surveys and monitorings in offshore pilot oyster reefs and experimental seafloor areas showed (i) that brown crabs, lobsters and oysters co-occur in these subtidal environments and (ii) interact with each other. Manipulative experiments indicated (iii, iv) that both predators consume oysters, (v) that medium-sized to large oysters are safe from brown crabs, and (vi) that large oysters are relatively safe from lobsters. They also found (vii) that the presence of common mussels (Mytilus spp.), as an alternative and more profitable prey, and (viii) the formation of larger and heavier oyster clumps, that are more difficult to handle, can reduce predation on oysters. Furthermore, they showed (ix) that the presence of brown crab conspecifics and (x) lobsters in natural abundances can nonconsumptively limit oyster consumption of brown crabs through intimidation mediated by (xi) brown crab- and (xii) lobster-released waterborne predator cues detected by brown crabs which indicates naturally underlying mechanisms regulating and limiting predation on oysters. Thereby, this study provides fundamental knowledge that is essential to understand predator-prey interactions in offshore oyster reefs and to facilitate ecological reef restoration.